2018
DOI: 10.4172/2576-389x.1000121
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability to Various Growth Conditions of Biofilm Associated Extended-Spectrum-Beta-Lactamases Producing Bacteria

Abstract: Extended-Spectrum β-Lactamase (ESBL) producing bacteria are becoming increasingly prevalent in biofilmassociated infections. Bacteria form biofilms that allow their survival in hostile environments. The amount of formed biofilm is affected by external environmental factors. This study investigates the effect of specific parameters (media type, incubation condition, and growth stage) on the amount of produced biofilm on antibiotic resistant bacterial strains, Escherichia coli (CTX-M-15, TEM-3, and IMP-type) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Bacterial biofilms are recognised as an important cause of many infections as 65-80% of all bacterial infections are related to biofilm formation [10][11][12]. Studies have shown that specific physiological growth conditions and genetic interactions within the biofilms cause a dramatic increase in intolerance to the antimicrobial agents, as well as the association between antibiotic resistance and biofilm formation [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial biofilms are recognised as an important cause of many infections as 65-80% of all bacterial infections are related to biofilm formation [10][11][12]. Studies have shown that specific physiological growth conditions and genetic interactions within the biofilms cause a dramatic increase in intolerance to the antimicrobial agents, as well as the association between antibiotic resistance and biofilm formation [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Although some surveys have shown that different growth conditions influence biofilm formation and, in turn, the association with antibiotic resistance [14], how the growth conditions affect the biofilm-related-gene expression was not well elucidated in CRE. Specifically, how the growth condition influences the expression of the genes responsible for the bacterial cell communication pathways in CRE.…”
Section: Introductionmentioning
confidence: 99%